DEVELOPMENT OF EXPLANATORY TEXT WRITING EVALUATION TOOLS BASED ON A PROCESS APPROACH (PENGEMBANGAN ALAT EVALUASI MENULIS TEKS EKSPLANASI BERBASIS PENDEKATAN PROSES) - Ramadhanti, Dina; Yanda, Diyan Permata; Ghazali, A Syukur; Hasanah, Muakibatul; Harsiati, Titik (Jurnal Gramatika, 2019)
ABSTRACTEvaluation in writing is one of the efforts in improving competence in writing, in addition to planning teaching programs based on the writing process. However, evaluation in writing is not intended to improve students' understanding in writing, even writing is seen as a straightforward product, not produced through a repetitive process. Therefore, this study aims to produce a product in the form of an explanatory text writing evaluation tool based on a process approach. By using the ADDIE development model, it was designed an evaluation tool according to the writing process carried out by students in addition to paying attention to the task environment and long-term memory of students. The writing process is used as a reference in developing evaluation tools, ranging from planning, translation (developing ideas and ideas), and reviewing (evaluation and revision). Planning becomes the initial stage for students to gather ideas and generate memory by writing a writing framework in the form of a mind map. Translation is an effort to develop the writing framework into explanatory text by taking into account the linguistic structure and rules of the text. Review in the form of evaluating or evaluating the written text, then revising according to the writing criteria. The writing process that is done in stages is complemented by hard think-aloud procedures so students can asking the question to themselves to monitor writing activities. Keywords: evaluation tools, explanatory text, a process approach  ABSTRAKEvaluasi dalam menulis menjadi salah satu upaya dalam meningkatkan kompetensi dalam menulis, selain merencanakan program pengajaran yang berbasis proses dalam menulis. Akan tetapi, evaluasi dalam menulis dilakukan tidak bertujuan untuk meningkatkan pemahaman peserta didik dalam menulis, bahkan tulisan dipandang sebagai produk yang langsung jadi, bukan dihasilkan melalui proses yang berulang. Oleh karena itu, penelitian ini bertujuan untuk menghasilkan produk berupa alat evaluasi menulis teks eksplanasi berbasis pendekatan proses. Dengan menggunakan model pengembangan ADDIE, dirancang alat evaluasi  sesuai proses menulis yang dilakukan peserta didik di samping memperhatikan lingkungan tugas dan memori jangka panjang peserta didik. Proses menulis yang dijadikan acuan dalam mengembangkan alat evaluasi, mulai dari perencanaan, penerjemahan (mengembangkan ide dan gagasan), dan peninjauan kembali (evaluasi dan revisi). Perencanaan menjadi tahapan awal bagi peserta didik untuk mengumpulkan gagasan dan membangkitkan memori dengan cara menulis kerangka tulisan dalam bentuk peta pikiran. Penerjemahan menjadi upaya untuk mengembangkan kerangka tulisan menjadi teks eksplanasi dengan memperhatikan struktur dan kaidah kebahasaan teks. Peninjauan kembali dalam bentuk menilai atau mengevaluasi teks yang ditulis, lalu dlakukan revisi sesuai kriteria penulisan. Proses menulis yang dilakukan secara bertahap ini dilengkapi dengan prosedur berpikir keras (think aloud) sehingga peserta didik dapat bertanya kepada dirinya sendiri untuk memantau aktivitas menulis yang dilakukan. Kata Kunci: Alat evaluasi, teks eksplanasi, pendekatan proses